Hydrogen as an energy vector to optimize the energy exploitation of a self-consumption solar photovoltaic facility in a dwelling house - Í\~nigo Martín-García; Enrique Rosales-Asensio; Alberto González-Martínez; Stefano Bracco; Federico Delfino; Miguel de Simón-Martín (Energy Reports, 2020)
Solar photovoltaic (PV) plants coupled with storage for domestic self-consumption purposes seem to be a promising technology in the next years, as PV costs have decreased significantly, and national regulations in many countries promote their installation in order to relax the energy requirements of power distribution grids. However, electrochemical storage systems are still unaffordable for many domestic users and, thus, the advantages of self-consumption PV systems are reduced. Thus, in this work the adoption of hydrogen systems as energy vectors between a PV plant and the energy user is proposed. As a preliminary study, in this work the design of a PV and hydrogen-production self-consumption plant for a single dwelling is described. Then, a technical and economic feasibility study conducted by modeling the facility within the Homer Energy Pro energy systems analysis tool is reported. The proposed system will be able to provide back not only electrical energy but also thermal energy through a fuel cell or refined water, covering the fundamental needs of the householders (electricity, heat or cooling and water). Results show that, although the proposed system effectively increases the energy local use of the PV production and reduces significantly the energy injections or demands into/from the power grid, avoiding power grid congestions and increasing the nano-grid resilience, operation and maintenance costs may reduce its economic attractiveness for a single dwelling.
Keywords: 330; Hydrogen; Solar photovoltaics; Energy vector; Power storage; Smart grids; Nano-grids